An investigation of psychological responses to COVID-19 in Irish healthcare workers: longitudinal quantitative and nested qualitative study [version 1; peer review: 2 approved] - Donal G. Fortune; Helen L. Richards; Andrew Wormald; Kieran O Connor; Margaret McKiernan; Pablo Najt; Amanda O Dwyer; Edmond O Dea; Paul Burke; Joseph Eustace (HRB Open Research, 2021)
COVID-19 is an unprecedent occurrence in modern times and individuals who work within healthcare settings, face a broad array of challenges in responding to this worldwide event. Key information on the psychosocial responses of such healthcare workers (HCWs) in the context of COVID-19 is limited and in particular there is a need for studies that utilise longitudinal methods, an overarching theoretical model, and use of a cohort of participants within a defined geographical area across acute and community settings. The work packages making up the current research project use quantitative and qualitative methods to examine the psychological sequelae for HCWs in the context of COVID-19 in geographically adjacent healthcare areas (South and Mid-West of Ireland) across four time points (induction, 3 months, 6 months, and 1 year follow-up). The quantitative arm of the project (WP 1) utilises the Common-Sense Model of Self-Regulation (CSM-SR) and examines a number of key psychological factors pertinent to this model including perceptions about COVID-19 and infection more generally, coping, formal and informal support and a number of impact variables including mood, sleep quality, and perceptions of stigma. The qualitative study (WP 2) will address HCWs experiences of working during the pandemic, ascertain any additional areas of psychological functioning, environmental and workplace factors and resources that may be utilised by HCWs and that are not assessed by the quantitative study protocol, focusing particularly on those staff groups typically underrepresented in previous studies.